Managing global portfolios - Stoakes, Chris ed. (Euromoney Publications LondonGB, 1989)
Examines aspects such as liability matching; asset allocation; duration based asset allocation; manager selection and manager style; indexation; comparison international indices; dynamic hedging and the use of derivatives, managing currency risk in overseas investments; fixed income management; block, programme and off exchange trading; company accounts worldwide; performance measurement; pension scheme reporting; and settlement and custody.